2011
DOI: 10.1074/jbc.m111.276444
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Convergence of Bacterial and Eukaryotic Surface Order

Abstract: Background: Living cells maintain a fluid membrane at their surface. Results: Bacteria and eukaryotes display comparable surface order. Transmembrane proteins order cell membranes in the absence of sterol (Bacteria) and disorder in its presence (Eukarya). Conclusion: Bidirectional ordering may provide a means to achieve similar barrier properties despite compositional differences. Significance: Nature may use different protein/lipid combinations to standardize cell surface order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…1B), suggesting a mechanistic connection. However, these synthetic liposomes are limited models for live cell membranes, most importantly because they lack cholesterol and integral membrane proteins, which make up a major fraction of surface area in biological membranes and contribute dramatically to their stabilities (56). However, the quantitative agreement between the onset concentration of both maximal cell injury (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1B), suggesting a mechanistic connection. However, these synthetic liposomes are limited models for live cell membranes, most importantly because they lack cholesterol and integral membrane proteins, which make up a major fraction of surface area in biological membranes and contribute dramatically to their stabilities (56). However, the quantitative agreement between the onset concentration of both maximal cell injury (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological signifi cance of the hydroxylation remains unclear. In S. cerevisiae , complex sphingolipids corresponding living cells could prevent the membrane from packing ( 32,42 ). The amount of immobile molecules markedly increased in the sur2 ⌬ csg1 ⌬ csh1 ⌬ mutant with the decrease in ergosterol content containing the P13 fraction ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for lipid-dependent functional domains has been reported for Bacillus subtilis (29), and there is evidence for lateral membrane heterogeneity in Gloeobacter violaceus (30), a hopanoid-producing cyanobacterium. Interestingly, it has been suggested that the averaged order of eukaryotic plasma membranes and bacterial inner membranes lacking hopanoids converge (31). These studies imply that bacteria that lack hopanoids may use alternate mechanisms for achieving lateral heterogeneity and modulating membrane order.…”
Section: Cholesterol and Diplopterol Modulate The Order And Phase Behmentioning
confidence: 99%